Trends in mortality due to non-communicable diseases in the Brazilian adult population: national and subnational estimates and projections for 2030 - Deborah Carvalho Malta; Bruce Bartholow Duncan; Maria Inês Schmidt; Renato Teixeira; Antonio Luiz Pinho Ribeiro; Mariana Santos Felisbino-Mendes; Ísis Eloah Machado; Gustavo Velasquez-Melendez; Luisa Campos Caldeira Brant; Diego Augusto Santos Silva; Valéria Maria de Azeredo Passos; Bruno R Nascimento; et al. (BMC, 2020)
Abstract Background Monitoring and reducing premature mortality due to non-communicable diseases (NCDs) is a global priority of Agenda 2030. This study aimed to describe the mortality trends and disability-adjusted life years (DALYs) lost due to NCDs between 1990 and 2017 for Brazil and to project those for 2030 as well as the risk factors (RFs) attributed deaths according to estimates of the Global Burden of Disease Study. Methods We analyzed cardiovascular diseases, chronic respiratory diseases, neoplasms, and diabetes, and compared the mortality rates in 1990 and 2017 for all of Brazil and states. The study used the definition of premature mortality (30-69 years) that is used by the World Health Organization. The number of deaths, mortality rates, DALYs, and years of life lost (YLL) were used to compare 1990 and 2017. We analyzed the YLL for NCDs attributable to RFs. Results There was a reduction of 35.3% from 509.1 deaths/100,000 inhabitants (1990) to 329.6 deaths/100,000 inhabitants due to NCDs in 2017. The DALY rate decreased by 33.6%, and the YLL rate decreased by 36.0%. There were reductions in NCDs rates in all 27 states. The main RFs related to premature deaths by NCDs in 2017 among women were high body mass index (BMI), dietary risks, high systolic blood pressure, and among men, dietary risks, high systolic blood pressure, tobacco, and high BMI. Trends in mortality rates due to NCDs declined during the study period; however, after 2015, the curve reversed, and rates fluctuated and tended to increase. Conclusion Our findings highlighted a decline in premature mortality rates from NCDs nationwide and in all states. There was a greater reduction in deaths from cardiovascular diseases, followed by respiratory diseases, and we observed a minor reduction for those from diabetes and neoplasms. The observed fluctuations in mortality rates over the last 3 years indicate that if no further action is taken, we may not achieve the NCD Sustainable Development Goals. These findings draw attention to the consequences of austerity measures in a socially unequal setting with great regional disparities in which the majority of the population is dependent on state social policies.